Simulação do fluxo hídrico subterrâneo por estimativa de parâmetros usando cargas hidráulicas observadas: caso do Cariri Cearense, Brasil - Souza, Cláudio Damasceno de (2019)
The main objective of this research is to use a computer code to simulate groundwater flow in an area in the south of the state of Ceará situated between the cities of Crato, Juazeiro do Norte and Barbalha, in the “Cariri” Valley. The computer code used was MODFLOW, a 3-D finite difference groundwater flow model. Two different scenarios were simulated: the rainy and the dry season. Besides, a code using the computer language FORTRAN was developed, which proposes an alternative to calibrate the model using hydraulic gradients instead of the usual hydraulic heads as the “objective” functions. The results indicate the behavior of the groundwater flow in the study area for sceneries dry and wet. The iterative method of calibration has proven to be dependent on the amount of data potentiometric level of the wells and its uniform distribution in the simulated area.